Neurogenic heterotopic ossification after a stroke: diagnostic and radiological challenges - Pek, Chong Han (Singapore Med J, 2014)
Heterotopic ossification (HO) is the aberrant formation of ectopic bone within the soft tissues, of which the aetiology is usually either traumatic or neurogenic. Neurogenic HO is a known but uncommon complication that occurs after a cerebral or spinal insult. The condition may present with a spectrum of symptoms and is often difficult to diagnose clinically. Although different imaging modalities have been used to diagnose HO, clinicians and radiologists may occasionally encounter radiological features of HO that may mimic other disease conditions. We herein report a rare case of neurogenic HO occurring in the non-paretic limb of a patient, and the diagnostic and radiological challenges encountered.